Unexpected high platelet counts in a potential platelet donor: A clue to essential thrombocythemia - Navkudkar, Anisha (Asian J Transfus Sci, 2020)
Essential thrombocythemia (ET) (primary thrombocythemia) is a nonreactive, chronic myeloproliferative clonal disorder in which sustained megakaryocyte proliferation leads to an increase in the number of circulating platelets. It is silent disorder and is diagnosed as high platelet counts with or without associated symptoms or as an accidental finding. We, hereby, report a case of ET as an incidental finding during screening of a potential platelet donor. Donors with high platelet count should be investigated properly to rule out ET. The role of transfusion medicine specialist is not only to recruit donors but also to identify such donors during screening and counsel them for detailed investigation and proper management.